Catalytic wet peroxide oxidation of aniline in wastewater using copper modified SBA-15 as catalyst. Issue 3 (1st February 2016) - Kong, Liming; Zhou, Xiang; Yao, Yuan; Jian, Panming; Diao, Guowang
Abstract : SBA-15 mesoporous molecular sieves modified with copper (Cu-SBA-15) were prepared by pH-adjusting hydrothermal method and characterized by X-ray diffraction, BET, transmission electron microscopy, UV–Vis and 29 Si MAS NMR. The pH of the synthesis gel has a significant effect on the amount and the dispersion of copper on SBA-15. The Cu-SBA-15(4.5) (where 4.5 denotes the pH value of the synthesis gel) modified with highly dispersed copper was used as catalyst for the oxidation of aniline by H2 O2 . The Cu-SBA-15(4.5) shows a higher catalytic activity compared to CuO on the surface of SBA-15. The influences of reaction conditions, such as initial pH of the aqueous solutions, temperature, as well as the dosages of H2 O2 and catalyst were investigated. Under weakly alkaline aqueous solution conditions, the aniline conversion, the H2 O2 decomposition and the total organic carbon (TOC) removal could be increased significantly compared to the acid conditions. The percentage of leaching Cu 2+ could be decreased from 45.0% to 3.66% when the initial pH of solution was increased from 5 to 10. The TOC removal could be enhanced with the increases of temperature, H2 O2 and catalyst dosage, but the aniline conversion and H2 O2 decomposition change slightly with further increasing dosage of catalyst and H2 O2 . At 343 K and pH 8.0, 100% aniline conversion and 66.9% TOC removal can be achieved under the conditions of 1.0 g/L catalyst and 0.05 mol/L H2 O2 after 180 min. Although copper might be slightly leached from catalyst, the homogeneous Cu 2+ contribution to the whole catalytic activity is unimportant, and the highly dispersed copper on SBA-15 plays a dominant role.